(untitled) (Muitas Vozes, 2021)
This paper presents a semantic analysis for a tweet published by Gregório Duvivier, which reads: “É fake que o príncipe fez suruba gay e bateu em mendigo. Ele não é príncipe.” ‘It is false that the prince has joined a gay gangbang and beated a tramp’. This utterance bears a famous puzzle in the field of Philosophy of Language, for it contains a definite description (o príncipe – ‘the prince’). Sentences like this are known from Russell’s paper On denoting (1905), since they can have sense but still lack reference. This author highlights that definite descriptions convey the information that there is one and only one prince of Brazil, and the inexistence of such an individual would render this sentence false. Strawson (1950), on the other hand, believes this sentence would not be false, but invalid, because a lack of reference would affect the existence presupposition triggered by the definite description. Since it is part of the implicita and not part of the asserted information of the proposition, the lack of reference concerns the felicity conditions of the utterance. As a consequence, we claim that the tweet under analysis manipulates the existence presupposition by metalinguistic negation (HORN, 2001 [1989]) without cancelling it, because the retification is driven just to the predicate inside the definite description and not to the existential quantifier. For that reason, Gregorio’s observation preserves the information that this individual has participated in the events of the main clause but the identification of such an individual by the hearer is done by pragmatic means, through extralinguistic knowledge. Thus, this analysis demonstrates how elementary principles both from Semantics and Pragmatics work, building them from a sentence extracted from real speech interaction.